I Must Betray You - Sepetys, Ruta (New York : Philomel Books, 2022)
In a country governed by isolation, fear, and a tyrannical dictator, seventeen-year-old Cristian Florescu is blackmailed by the secret police to become an informer, but he decides to use his position to try to outwit his handler, undermine the regime, give voice to fellow Romanians, and expose to the world what is happening in his country. Includes author's note.
Includes bibliographical references.
Keywords: Spies -- Juvenile fiction; Families -- Juvenile fiction -- Romania; Dictatorship -- Juvenile fiction; Revolutions -- Juvenile fiction; Spies -- Fiction; Families -- Fiction -- Romania; Dictatorship -- Fiction; Revolutions -- Fiction; Romania -- Juvenile fiction -- History -- Revolution, 1989; Bucharest (Romania) -- Juvenile fiction -- History -- 20th century; Romania -- Fiction -- History -- Revolution, 1989; Bucharest (Romania) -- Fiction -- History -- 20th century; Historical fiction